EFEK SAFETY TALK TERHADAP PERILAKU K3 DI PROYEK APARTEMEN GRAND DHARMAHUSADA LAGOON SURABAYA - Romy Ananda Muslim; Feri Harianto (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2021)
The implementation of construction projects has a high risk of work accidents, one of the causes is the low level of awareness and understanding of workers about Occupational Health and Safety (OHS). One way to increase awareness and understanding of OHS is through safety talk activities. The purpose of this study was to determine the differences in OHS behavior between workers who followed and did not follow the safety talk. This research method used experiment design with safety talk treatment. Measurement of OHS behavior using a questionnaire with workers as respondents, a sample size of 15 people in each experimental group. The analysis used is the difference test with independent t-test analysis. The results showed a significant difference between workers who followed and did not participate in the safety talk with a value of 0.00 <0.05. Workers who take safety talk have better OHS behavior than workers who don't.